Polarization and hate speech with gender bias associated with politics: analysis of interactions on Twitter - Blanco-Alfonso, Ignacio (2022)
The spread of hate speech through social media contributes to poisoning the public sphere and undermining the quality of liberal democracies. This type of discourse is particularly virulent against the political class and against feminism. Taking this reality as a starting point, this research will attempt to identify the gender bias in hate speech in the political sphere: do female politicians receive more verbal attacks than their male counterparts, not because they are politicians, but because they are women? Do female politicians receive more emotional polarity in the mentions they receive on Twitter than their male counterparts? Through discourse analysis using PLN techniques for emotion detection and text mining on a corpus of 3,483,232 tweets collected from 20 accounts of Spanish politicians, it is found that the messages received by women politicians concentrate more emotional polarity than men's, but not more hatred, which is slightly higher in men. It also confirms that sexist and misogynist expressions are used to denigrate women and, by extension, feminism, which makes hate speech a type of information disorder.